Effect of CaF2/P2O5 ratios on physical and mechanical properties of novel CaO-Na2O-B2O3-SiO2 glasses - Zhi, Wei Loh; Mohd Zaid, Mohd Hafiz; Awang Kechik, Mohd Mustafa; Yap, Wing Fen; Yaakob, Yazid; Mayzan, Mohd Zul Hilmi; Shahira Liza; Wei, Mun Cheong (Elsevier, 2022)
This paper outlines the fabrication of bioactive glass derived from waste eggshells as a source of calcium via the melt and water quenching method. The influence of the CaF2/P2O5 ratio on the physical, structural and mechanical properties of bioglass samples was investigated. XRD confirmed the amorphous structure, while the presence of Si–O–Si, P–O, and C–O indicated the formation of bioglass samples. It was found that increasing CaF2 content with appropriate P2O5 content could improve the mechanical properties of the bioglass. The increase in density can significantly impact the bioglass samples’ compressive strength and vickers microhardness. The bioglass with CaF2/P2O5 ratio of 6/4 possessed better properties, showing the optimal compressive strength (48.98 ± 0.11 MPa) and vickers microhardness (3.09 ± 0.07 GPa), which is compatible with the human enamel and commercial bioglass. Thus, the findings seem to contribute to a prospective cost-effective waste-derived bioglass system used in dental applications.